PRESENT SITUATION ANALYSIS: STUDENTS’ EARLY CHARACTERISTICS IN WRITING FOR ACADEMIC PURPOSES - Audi Yundayani (University of Kuningan, 2018)
Present situation analysis is considered to be the umbrella that embraces students’ lacks in language proficiencies. The aims of this study were to (1) find out current students’ writing competence level; (2) identify students’ entry behaviors and characteristics; (3) identify students’ perception concerning with writing skill for academic purposes at non-English education study programs of STKIP Kusuma Negara Jakarta. The descriptive inquiry was used in identifying students’ present situation. The respondents were non-English education study programs students of STKIP Kusuma Negara Jakarta in the academic year 2016-2017 and English lecturers. Non-English education study programs students of STKIP Kusuma Negara Jakarta had low-level writing competence for academic purposes, in the area of academic styles and genres based on their disciplines. Their previous experience in studying English was different with college requirement. They were not interested in studying writing for an academic purpose due to it was difficult and made them confusing. Most of them never practiced and learned it seriously but they realized the importance of having competence in writing for academic purposes, especially related with the learning process in the university level.Keywords: present situation analysis, writing for academic purposes, descriptive inquiry